An Estimate of Wolverine Density for the Canadian Province of Alberta - Jason T. Fisher; Mehnaz Jahid; Robin Gutsell; Anne Hubbs; Laura L. E. Cowen; Mirjam Barrueto; Nicole Heim; John Paczkowski (Ecology and Evolution)
ABSTRACT Wolverines (Gulo gulo) are a circumboreal species that has experienced substantial range reduction worldwide. In Canada, the wolverine has been extirpated entirely from the east, and from prairie regions in the west. The province of Alberta holds the south‐central portion of wolverines' Canadian range, and there they have been designated as Data Deficient since 2001 due to a historical lack of information. Our aim was to provide a first approximation of a wolverine abundance estimate at the provincial scale to inform science‐based management as well as status designation. We synthesised existing density estimates and wolverine–habitat relationships to create a province‐wide density estimate for wolverines. Densities were derived from five landscapes, spanning protected National Parks in the Rocky Mountains, the highly developed Foothills and the northcentral and northwestern boreal forests. Densities were estimated using spatially explicit capture–recapture (SECR) models. Densities ranged from 6.74 wolverines/1000 km2 in the northwest boreal to 0.71 wolverines/1000 km2 in the foothills. The proportion of adults was based on a study from the northwest, which estimated 57% adults to 43% subadults. Extrapolating densities across natural subregions (bioclimatic ecoregions), based on known habitat relationships, it was estimated that there were 955 wolverines in the province, of which 544 were adults. This number falls well below an IUCN threshold for a legally listed species; we suggest a reassessment of the wolverine status in Alberta and considering commensurate conservation actions.